Drug use and the influence on kissing among men who have sex with men in Melbourne, Australia. (January 2020) - Chow, Eric PF; Ong, Jason J; Vodstrcil, Lenka A; Fairley, Christopher K
The use of drugs is not uncommon among gay, bisexual and other men who have sex with men (MSM). Kissing has been recently identified as a risk factor for gonorrhoea. This study aimed to examine the proportion of MSM who used drugs and how specific drugs influence the likelihood of kissing. We conducted a cross-sectional survey among MSM attending the Melbourne Sexual Health Centre between March 2016 and February 2017. Participants reported their use of eleven specific drugs in the last three months and whether they felt the drug influenced them to kiss someone. Four thousand, three hundred and ninety-one MSM were included in the analysis; 63.1% ( n  =   2772) used at least one drug in the last three months and 36.6% ( n  =   1605) used ≥2 drugs. Poppers (44.8%), marijuana (30.8%) and ecstasy (19.1%) were the three most common drugs used among MSM in the last three months. 80.4% of ecstasy users and 74.3% of gammahydroxybutyrate users reported the drug made them much more likely to kiss someone. The majority of MSM reported that the use of heroin (63.6%) and Viagra/Cialis (60.7%) did not influence their kissing behaviour. Drug use is common among sexually active MSM in Melbourne. Most reported the use of ecstasy would increase their likelihood of kissing someone.